2022
DOI: 10.1101/2022.06.30.22277102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low back pain service utilization and costs: association with timing of first-line services for individuals initially contacting a primary care provider. A retrospective cohort study

Abstract: Background: Low back pain (LBP) is prevalent, costly, and a common reason for a visit to a primary care provider (PCP). Guidelines recommend a stepped approach to management. Objective: For individuals with LBP initially contacting a PCP, examine the association between the incorporation of first-line therapies, use of second- and third-line services and total episode cost. Design: Retrospective cohort study Setting/Patients: National sample of individuals with non-surgical LBP occurring in 2017-2019. Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 43 publications
(98 reference statements)
1
14
0
Order By: Relevance
“…First, an identical study of individuals with LBP initially contacting a PCP also found low rates of incorporation of AC, MT, CMT, OMT, and Acu. 47 Second, a previous study found a low proportion of individuals with NP initially contacting a PCP have timely incorporation of guideline-concordant non-pharmacologic and non-interventional therapies. 35 This study expands on this to explore more detailed distribution of episodes by timing of incorporation of AC, MT, CMT, OMT, and Acu.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, an identical study of individuals with LBP initially contacting a PCP also found low rates of incorporation of AC, MT, CMT, OMT, and Acu. 47 Second, a previous study found a low proportion of individuals with NP initially contacting a PCP have timely incorporation of guideline-concordant non-pharmacologic and non-interventional therapies. 35 This study expands on this to explore more detailed distribution of episodes by timing of incorporation of AC, MT, CMT, OMT, and Acu.…”
Section: Discussionmentioning
confidence: 99%
“…The study design was identical to a previous study of LBP conducted by the same author group. 47 De-identified enrollment records and administrative claims data for individuals with NP were included in an enrollee database. HCP de-identified demographic information and professional licensure status was included in a HCP database.…”
Section: Study Design Population Setting and Data Sourcesmentioning
confidence: 99%
See 3 more Smart Citations